THE ERRORS OF POPPER: A CRITICISM (Andamios, Revista de Investigación Social, 2008)
In this work, the author criticizes some aspects of Popper’s philosophy, including his emphasis on the necessity of committing errors, his assertion that we don’t learn by repetition or routine, his criticism of inductivism, the parallels between his scientific philosophy and his political philosophy, his excessive emphasis on the role of criticism, Popperian Darwinism, the contradiction between his “situational logic” and his “methodical individualism,” and his false affirmations about war. The author also points out some of the inconsistencies of the Austrian philosopher.
Keywords: Science; criticism; errors; contemporary problems; inconsistencies